Developmental Research: An Android-Based Arabic Language Learning Application as a Means to Improve Middle School Students' Learning Outcomes - Al amin, Yusra; Najah, Zughrofiyatun (WISE Pendidikan Indonesia, 2023)
The aim of this research is to: (1) explain the Android-based interactive learning media for Arabic language in the eighth grade, (2) describe the feasibility of the Android-based interactive learning media for Arabic language in the eighth grade, (3) elucidate the effectiveness of the Android-based interactive learning media for Arabic language in the eighth grade in the learning process, (4) explain the difference in student learning outcomes before and after the use of Android-based interactive learning media for Arabic language in the eighth grade. The type of research used is Research and Development (R&D), using the ADDIE development model. The results of this research indicate that (1) the product resulting from this research and development is an Android-based application that can be accessed on all Android versions, (2) the product testing results have a validity rate of 89.2% according to subject matter experts and 86.5% according to media experts in the product validity table. These results fall into the highly feasible category, meaning they do not require revisions and can be implemented in the learning process. Therefore, the developed learning media is highly feasible. (3) The effectiveness test of the product falls into the category of moderately effective in small and large-scale trials, with percentages of 61.82% and 69.16%, respectively. (4) The difference in student learning outcomes, with an average pre-test score of 86 and a post-test score of 53, shows a significance value greater than the t-critical value (21.03845 > 1.699 at α = 0.05), which leads to the conclusion that the use of Android-based interactive learning media in the eighth grade can improve student learning outcomes.